Children and young adults with CF in the USA have better lung function compared with the UK. Issue 3 (25th September 2014) - Goss, Christopher H; MacNeill, Stephanie J; Quinton, Hebe B; Marshall, Bruce C; Elbert, Alexander; Knapp, Emily A; Petren, Kristofer; Gunn, Elaine; Osmond, Joanne; Bilton, Diana
Abstract : Background: People with cystic fibrosis (CF) are managed differently in the USA and UK providing an opportunity to learn from differences in practice patterns. Objectives: To compare cross-sectional demographics, practice patterns and clinical outcomes between US and UK CF patients. Methods: This was a cross-sectional study using 2010 data from patients in the US Cystic Fibrosis Foundation and the UK Cystic Fibrosis patient registries. The a priori outcome measures of interest were lung function and nutritional status. Descriptive statistics and two sample comparisons were performed. Stratification and multivariable linear regression were used to adjust for confounding. Results: The study cohort included 13 777 children and 11 058 adults from the USA and 3968 children and 3965 adults from the UK. In children, mean body mass index centiles were similar. Lung function (FEV1 and FVC% predicted) was significantly higher in US patients ages 6–25 years of age. In a regression model adjusted for only age, FEV1 % predicted was on average 3.31% of predicted (95% CI 2.65 to 3.96) higher in the USA compared with the UK. When adjusted for age, age at diagnosis, gender, pancreatic insufficiency and genotype, FEV1 % predicted was on average 3.03% of predicted (95% CI 2.37 to 3.69) higher in the USA compared with the UK These differences persisted despite adjustment for possible confounders. Hypertonic saline and dornase alfa were much more commonly prescribed in US children. Conclusions: Children and young adults with CF have better lung function in the USA compared with the UK despite similar nutritional status.